1971
DOI: 10.1021/jm00293a002
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q. 114. Biosynthesis of coenzymes Q by malarial parasites. 2. Coenzyme Q synthesis in blood cultures of monkeys infected with malarial parasites (Plasmodium falciparum and P. knowlesi)

Abstract: Aq NaOH (30%) was added dropwise with vigorous stirring to maintain the pH between 10 and 10.5. After addn of about 10 ml of aq NaOH, the pH remained const and the Et20 layer was removed to give an oil which crystd from heptane: 4-methoxy-1-naphthol, mp 126-128°(lit.18 124-125°); 5-metho.xy-l-naphthol, mp 137-138°(lit.19 135-136°); 8-methoxy-1-naphthol, mp 55-57°(lit.13 55-56°); 3-methoxy-2-naphthol, mp 107-108°(lit.20 108°); 6-methoxy-2-naphthol, mp 148-149°(lit.21 136-137°) (Anal. (CnII.oOs) C, H); 7-methoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…The reaction was functionally isolated from other respiratory complexes by the action of atovaquone and cyanide for complexes III and IV, respectively. The native ubiquinone of P. falciparum is CoQ 8 (42,43), but as this is too hydrophobic and cannot be used as an exogenous substrate, we assayed PfNDH2 activity using the more hydrophilic short-chain analogs CoQ 1 (with only one isoprenoid unit in the side chain) and DB, which contains a 10-carbon linear saturated side chain. Quinone-dependent oxidation of NADH displayed Michaelis-Menten kinetics ( (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was functionally isolated from other respiratory complexes by the action of atovaquone and cyanide for complexes III and IV, respectively. The native ubiquinone of P. falciparum is CoQ 8 (42,43), but as this is too hydrophobic and cannot be used as an exogenous substrate, we assayed PfNDH2 activity using the more hydrophilic short-chain analogs CoQ 1 (with only one isoprenoid unit in the side chain) and DB, which contains a 10-carbon linear saturated side chain. Quinone-dependent oxidation of NADH displayed Michaelis-Menten kinetics ( (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…P. falciparum mitochondria use a different homolog of ubiquinone (CoQ 8 ) than their mammalian host (42,43), and several antimalarial drugs show specificity for parasite CoQ, including the hydroxynaphthoquinones (13, 50). This strategy led to the development of atovaquone (20), an inhibitor of complex III (or bc 1 complex), which has been successful clinically, especially in combination with proguanil (Malarone), for the treatment of chloroquine-resistant infections (31).…”
Section: As Inhibition Of Pfndh2 Leads To a Depolarization Of Mitochomentioning
confidence: 99%
“…Schnell et al [29] found the presence of coenzyme Q 8 and coenzyme Q 9 in P. falciparum by using [ 14 C]PHBA to label the benzoquinone ring in infected blood from the monkey species Aotus trivirgatus. We suggest that, as coenzyme Q acts as an antioxidant, the host's organism could be forcing the parasite to produce di¡erent homologs in order to resist di¡erent kinds of oxidative damage imposed by the immune system [30].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of these isoprenoids to 4-hydroxybenzoate is performed by 4-hydroxybenzoate octaprenyltransferase (EC 2.5.1.39, PlasmoDB ID PF3D7_0607500) (118,119). Labeling studies in P. falciparum identify coenzyme Q isoforms coenzyme Q8 and Q9, which have 8 and 9 isoprene units (40-carbon and 45-carbon), respectively, in their side chains (120,121). Incorporation of labeled FPP results in the detection of coenzyme Q8, and incorporation of labeled GGPP detects coenzyme Q9 (120).…”
Section: Coenzyme Q (Ubiquinone)mentioning
confidence: 99%